2022
DOI: 10.1021/jacs.2c06808
|View full text |Cite
|
Sign up to set email alerts
|

Class V Lanthipeptide Cyclase Directs the Biosynthesis of a Stapled Peptide Natural Product

Abstract: Lanthipeptides are a class of cyclic peptides characterized by the presence of one or more lanthionine (Lan) or methyllanthionine (MeLan) thioether rings. These cross-links are produced by α,β-unsaturation of Ser or Thr residues in peptide substrates by dehydration, followed by a Michael-type conjugate addition of Cys residues onto the dehydroamino acids. Lanthipeptides may be broadly classified into at least five different classes, and the biosynthesis of classes I–IV lanthipeptides requires catalysis by LanC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
1
20
1
Order By: Relevance
“…Lanthipeptides are the largest subfamily of ribosomally synthesized and post-translationally modified peptides (RiPPs). These peptide natural products bear characteristic intramolecular lanthionine and/or labionin rings and are often referred to as lantibiotics due to their prevalent antimicrobial properties. , They are subdivided into five classes depending on their biosynthetic machinery. , Class III lanthipeptides are an emerging class, beginning with the report of their first member, labyrinthopeptins, in 2010. , Consistent with the literature, , our present bioinformatic analysis of 223,243 bacterial and archaeal genomes revealed that class III lanthipeptide biosynthetic gene clusters (BGCs) are widely distributed in bacterial phyla, with Actinobacteria being the most abundant and Firmicutes being the second most abundant harboring these BGCs. Compared to Actinobacteria, a known major source for class III lanthipeptide discovery, no class III lanthipeptide structures had been reported from Firmicutes when we initiated the present study, and now only andalusicin, amylopeptin, bacinapeptin, and paenithopeptin have been reported, still leaving class III lanthipeptides in Firmicutes significantly underexplored.…”
Section: Introductionsupporting
confidence: 73%
“…Lanthipeptides are the largest subfamily of ribosomally synthesized and post-translationally modified peptides (RiPPs). These peptide natural products bear characteristic intramolecular lanthionine and/or labionin rings and are often referred to as lantibiotics due to their prevalent antimicrobial properties. , They are subdivided into five classes depending on their biosynthetic machinery. , Class III lanthipeptides are an emerging class, beginning with the report of their first member, labyrinthopeptins, in 2010. , Consistent with the literature, , our present bioinformatic analysis of 223,243 bacterial and archaeal genomes revealed that class III lanthipeptide biosynthetic gene clusters (BGCs) are widely distributed in bacterial phyla, with Actinobacteria being the most abundant and Firmicutes being the second most abundant harboring these BGCs. Compared to Actinobacteria, a known major source for class III lanthipeptide discovery, no class III lanthipeptide structures had been reported from Firmicutes when we initiated the present study, and now only andalusicin, amylopeptin, bacinapeptin, and paenithopeptin have been reported, still leaving class III lanthipeptides in Firmicutes significantly underexplored.…”
Section: Introductionsupporting
confidence: 73%
“…S4, ESI†). The observed NOEs differ significantly from what is observed for ( Z )-Dhb residues in previously characterized lanthipeptides 30,31 (Fig. S5 and S6, ESI†) and linaridins.…”
contrasting
confidence: 78%
“…Recently, the class V lanthipeptide biosynthetic pathway was identified and characterized. A kinase/lyase pair (LanK/LanY) and a class I cyclase LanC were found to be responsible for the dehydration and cyclization reactions. , Apart from the difference between the biosynthetic enzymes, five classes of lanthipeptides can also be distinguished based on the biosynthetic machinery utilized by these enzymes. Class I LanB dehydratase uses glutamyl-tRNA Glu to activate the hydroxyl side chains of Ser/Thr residues followed by glutamate elimination , (Figure A).…”
Section: Introductionmentioning
confidence: 99%